ANALISIS DATA MINING DALAM DALAM MENENTUKAN DATA KELAYAKAN KARYAWAN DI RSUD BUKITTINGGI MENGUNAKAN ALGORITMA C 4.5 - Ridho, Muhammad; Kurnia, Dona; Darmawati, Gusnita (Jurnal Informatika UPGRIS, 2026)
Bukittinggi Regional Hospital has a lot of employee data that can be analyzed to determine employee eligibility levels based on certain performance and criteria. This research aims to apply the C4.5 algorithm in determining the suitability of employees at Bukittinggi Regional Hospital. Data mining methods are used to explore patterns and knowledge from historical employee data such as attendance, work discipline, achievements and superior evaluation results. The research process includes data collection, preprocessing, decision tree formation using the C4.5 algorithm, and evaluation of model results. The results of the research based on a decision tree based on high school education level, less suitable, 8.02.0, suitable, 12.0.0, and D3 and Bachelor's education levels, suitable, 28.07.0, less suitable, 16.05.0, show that the C4.5 algorithm is able to produce a classification model with a good level of accuracy in determining employee eligibility categories, namely suitable and unsuitable. It is hoped that the application of this method will help the management of Bukittinggi Regional Hospital in making more objective and efficient decisions regarding employee suitability.